Determinasi Artificial Intelligence Akuntansi di Praktek Mandiri Dokter Umum - Ratih, Nur Rahmanti; Kusuma, Marhaendra; Barreto, Carlos Afonso (Politeknik Negeri Jember, 2024)
This study aims to examine the influence of doctors' knowledge of the benefits of accounting, technical knowledge and demands of obligations on the implementation of artificial intelligence (AI) of accounting in independent general practitioner practice entities. Data from questionnaire answers to respondents as many as 167 general practitioners who open independent practice services. The research method uses a quantitative approach with hypothesis testing using multiple linear regression analysis to test factors that influence the implementation of AI of accounting and the Independent t-test mean difference test to test differences in doctors' perceptions based on their characteristics. The results of the multiple linear regression analysis test show that the factors that influence the implementation of AI of accounting are 1) doctors' knowledge of the benefits of accounting, 2) doctors' knowledge of basic accounting techniques, and 3) demands of obligations from stakeholders. The results of the Independent t-test test show that there is no difference in the perception of the need for AI of accounting between ASN and Non-ASN general practitioners. The originality of this study: testing the determination of the implementation of AI of accounting in independent general practitioner practice entities, and testing differences in perceptions of the implementation of AI of accounting between ASN and non-ASN general practitioners.